2010
DOI: 10.1007/s00216-010-4353-9
|View full text |Cite
|
Sign up to set email alerts
|

A multi-channel bioluminescent bacterial biosensor for the on-line detection of metals and toxicity. Part I: design and optimization of bioluminescent bacterial strains

Abstract: This study describes the construction of inducible bioluminescent strains via genetic engineering along with their characterization and optimization in the detection of heavy metals. Firstly, a preliminary comparative study enabled us to select a suitable carbon substrate from pyruvate, glucose, citrate, diluted Luria-Bertani, and acetate. The latter carbon source provided the best induction ratios for comparison. Results showed that the three constructed inducible strains, Escherichia coli DH1 pBzntlux, pBars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 55 publications
0
33
0
Order By: Relevance
“…Growth phase and cell's nutritional condition may influence not only the reporter expression, but also the envelope status, affecting ion permeability (Charrier et al, 2011;Kohlmeier et al, 2007). Thus, we evaluated the response of the transgenic E. coli golTSB reporter strain to Au and Cu ions under different conditions.…”
Section: Calibration Of the Transgenic E Coli Au-biosensormentioning
confidence: 99%
See 1 more Smart Citation
“…Growth phase and cell's nutritional condition may influence not only the reporter expression, but also the envelope status, affecting ion permeability (Charrier et al, 2011;Kohlmeier et al, 2007). Thus, we evaluated the response of the transgenic E. coli golTSB reporter strain to Au and Cu ions under different conditions.…”
Section: Calibration Of the Transgenic E Coli Au-biosensormentioning
confidence: 99%
“…In fact, most of the designed MerR-based biosensors display high sensitivity but low selectivity because the sensor proteins cross-react with a group of related metal ions (Harms, 2007;Hynninen and Virta, 2010;Magrisso et al, 2008). For example, previously constructed Cu biosensors based on CueR, the monovalent metal sensor of the MerR family, detect Cu but also Ag and Au, as the regulator is similarly sensitive to any of these metals (Charrier et al, 2011;Hakkila et al, 2004;Riether et al, 2001;Stoyanov and Brown, 2003). This makes the use of these bioreporters unsuitable for particular applications.…”
Section: Introductionmentioning
confidence: 97%
“…The detection range of Hg 2+ was from 5 nmol/L to 10 μmol/L, and distinct luminescence could be detected in 30 min. The use of recombinant luminescent bacteria based on the mer gene had the potential to be a proper method for online monitoring of bioavailable mercury, but many issues needed more research before field application (Charrier et al, 2011). One of the most important issues was to avoid the false negative problem.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that the bioluminescent As biosensors responded to other metals (e.g. Cd, Pb, Sn) with various detection limits (Hakkila et al, 2004;Charrier et al, 2011). This might attribute to different P ars and arsR sequences and lux reporter for the biosensors as it has been previously reported that the bioluminescent bacteria were not specific to only one metal but rather to a range of metals (Binet and Poole, 2000;Riether et al, 2001;Charrier et al, 2011).…”
Section: Characterization Of the Color-based As Bacterial Biosensormentioning
confidence: 91%